2022
DOI: 10.1002/term.3290
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of the effect of platelet rich fibrin matrix with and without peripheral blood mesenchymal stem cells on dental implant stability: A randomized controlled clinical trial

Abstract: Technological advances in the field of implantology have led to the concept of surface modifications to enhance implant stability by utilization of current concepts of tissue engineering and materials such as platelet concentrates and stem cells. The purpose of the present randomized controlled clinical trial was to evaluate and compare the effect of platelet rich fibrin matrix (PRFM) with and without peripheral blood mesenchymal stem cells (PBMSCs) on implant stability; by assessing the bone to implant contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The impact of platelet-rich fibrin on the stability of dental implants was evaluated, and it was shown that platelet-rich fibrin enhanced secondary implant stability, offering potential implications for clinical application [49]. The platelet-rich fibrin matrix was combined with peripheral blood mesenchymal stem cells to enhance implant stability, which was evaluated by measuring bone-to-implant contact using resonance frequency analysis [50,51]. This approach showed promise as a regenerative material for improving and reinforcing bone-to-implant contact, ultimately enhancing implant stability.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of platelet-rich fibrin on the stability of dental implants was evaluated, and it was shown that platelet-rich fibrin enhanced secondary implant stability, offering potential implications for clinical application [49]. The platelet-rich fibrin matrix was combined with peripheral blood mesenchymal stem cells to enhance implant stability, which was evaluated by measuring bone-to-implant contact using resonance frequency analysis [50,51]. This approach showed promise as a regenerative material for improving and reinforcing bone-to-implant contact, ultimately enhancing implant stability.…”
Section: Discussionmentioning
confidence: 99%